2013
DOI: 10.1177/1099800413496454
|View full text |Cite
|
Sign up to set email alerts
|

In Patients With Stable Heart Failure, Soluble TNF-Receptor 2 Is Associated With Increased Risk for Depressive Symptoms

Abstract: Objectives Researchers have proposed biological (inflammation) and psychological (depression) factors as potential mechanisms for poorer outcomes and readmissions in heart failure (HF) patients. However, studies investigating the link between inflammation and depressive symptoms in these patients are few. We examined the relationships between levels of the inflammatory markers C-reactive protein (CRP), interleukin (IL)-6, and soluble tumor necrosis factor receptor 2 (sTNR2) and depressive symptoms in HF outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Previously, it was shown that depression is accompanied by increased sTNF-R2 levels (Grassi-Oliveira et al 2009 ), while sTNF-R2 levels are also elevated in late life depression (Diniz et al 2010 ). In patients with stable heart failure, increased sTNF-R2 levels are associated with an increased risk of depression (Moughrabi et al 2014 ). In the Rizavi et al ( 2016 ) study, depression was not only accompanied by increased lymphocytic sTNF-R1, but also sTNF-R2 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was shown that depression is accompanied by increased sTNF-R2 levels (Grassi-Oliveira et al 2009 ), while sTNF-R2 levels are also elevated in late life depression (Diniz et al 2010 ). In patients with stable heart failure, increased sTNF-R2 levels are associated with an increased risk of depression (Moughrabi et al 2014 ). In the Rizavi et al ( 2016 ) study, depression was not only accompanied by increased lymphocytic sTNF-R1, but also sTNF-R2 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…These meta-analyses showed additionally that Th2 and Tregulatory (Treg) cytokines (including IL-10, IL4, and IL-5) were not significantly altered in major depression indicating that major depression is characterized by M1 and Th1 activation. There are also some reports that plasma levels of soluble TNF receptor 60 kDa (sTNF-R1) and 80 kDa (sTNF-R2) are elevated in depression (Grassi-Oliveira et al 2009 ; Moughrabi et al 2014 ; Rizavi et al 2016 ). These TNFα receptor subtypes act as decoy receptors by binding sTNFα thereby attenuating TNFα signaling and thus inhibiting TNFα activities (Selinsky et al 1998 ; Su et al 1998 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a reduction of TNF‐RII gene ( TNF‐RII ) mRNA level was found in Brodmann's area 46 in subjects with mood disorders, including major depressive disorders 12 . There was a significant relationship between sTNF‐RII and depression scores in heart failure patients even after adjustments for age, gender, BMI and heart failure aetiology 13 . Meanwhile, a higher sTNF‐RII level was shown to be associated with antidepressant use in women 14 .…”
Section: Introductionmentioning
confidence: 99%
“…12 There was a significant relationship between sTNF-RII and depression scores in heart failure patients even after adjustments for age, gender, BMI and heart failure aetiology. 13 Meanwhile, a higher sTNF-RII level was shown to be associated with antidepressant use in women. 14 Therefore, TNF-RII may play an important role in depressive disorder or antidepressant treatment.…”
mentioning
confidence: 99%
“…In fact, it has been documented that TNF-RII is related with depression [ 15 ]. Increased mRNA levels of TNF-α and TNF-RII in lymphocytes were found for depression patients [ 16 ], and increased levels of serum TNF-RII in heart failure and depression patients [ 17 ]. However, no significant correlation was found in the levels of TNF-α among depressed female patients [ 18 ].…”
Section: Introductionmentioning
confidence: 99%